Bridging acute and chronic stress effects on inflammation: protocol for a mixed-methods intensive longitudinal study - Seizer, Lennart; Pascher, Anja; Branz, Sonja; Schmitt, Nadine; Löchner, Johanna; Schuller, Björn W.; Rohleder, Nicolas; Renner, Tobias J. (BMC Psychology, 2025)
Acute stress triggers adaptive physiological responses—including transient increases in inflammatory cytokines—while chronic stress is associated with sustained inflammatory activity that may underlie the development of various disorders. Despite extensive research on each stress type individually, the transition and interaction between them remain underexplored. This study aims to address this gap by employing an intensive longitudinal measurement burst design. Healthy university students will be recruited and monitored over three one-week assessment bursts, spaced by three-month breaks. Participants will complete ecological momentary assessments four times daily, recording their emotional states, stress experiences, and daily incidents. Simultaneously, saliva samples will be collected at matching time points to measure biomarkers of immune and stress system activity. In addition, daily audio diaries will provide qualitative context through advanced speech analysis techniques. Data will be analyzed using a multi-level modeling approach to differentiate within-person dynamics from between-person variability, accounting for potential moderators. The findings are expected to shed light on how repeated acute stressors transition into chronic stress and how chronic stress burden may influence acute stress responses.
CRIS-Team Scopus Importer:2025-05-16
Keywords: Ecologcial momentary assessment; Inflammation; Intensive longitudinal data; Psychoneuroimmunology; Stress